1996
DOI: 10.1016/s0092-8674(00)81252-0
|View full text |Cite
|
Sign up to set email alerts
|

Agrin Acts via a MuSK Receptor Complex

Abstract: Formation of th neuromuscular junction depends upon reciprocal inductive interactions between the developing nerve and muscle, resulting in the precise juxtaposition of a differentiated nerve terminal with a highly specialized patch on the muscle membrane, termed the motor endplate. Agrin is a nerve-derived factor that can induced molecular reorganizations at the motor endplate, but the mechanism of action of agrin remains poorly understood. MuSK is a receptor tyrosine kinase localized to the motor endplate, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
569
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 628 publications
(589 citation statements)
references
References 44 publications
16
569
0
4
Order By: Relevance
“…Presynaptic differentiation is also aberrant in agrin and Musk mutant mice, as motor axons fail to stop or differentiate and instead wander throughout the muscle. Taken together with experiments showing that Musk is activated by agrin, these results indicate that agrin stimulation of Musk leads to clustering of critical musclederived proteins, including AChRs, activation of synapsespecific gene expression and the induction and/or reorganization of a retrograde signal for presynaptic differentiation (DeChiara et al, 1996;Gautam et al, 1996;Glass et al, 1996). Domains in Musk that are important for Musk signaling have been defined by introducing wild-type or mutant forms of Musk into Musk mutant muscle cell lines (Herbst and Burden, 2000;Zhou et al, 1999).…”
Section: Introductionmentioning
confidence: 80%
“…Presynaptic differentiation is also aberrant in agrin and Musk mutant mice, as motor axons fail to stop or differentiate and instead wander throughout the muscle. Taken together with experiments showing that Musk is activated by agrin, these results indicate that agrin stimulation of Musk leads to clustering of critical musclederived proteins, including AChRs, activation of synapsespecific gene expression and the induction and/or reorganization of a retrograde signal for presynaptic differentiation (DeChiara et al, 1996;Gautam et al, 1996;Glass et al, 1996). Domains in Musk that are important for Musk signaling have been defined by introducing wild-type or mutant forms of Musk into Musk mutant muscle cell lines (Herbst and Burden, 2000;Zhou et al, 1999).…”
Section: Introductionmentioning
confidence: 80%
“…These studies implicated motor neuron-derived Agrin, a glycosylated proteoglycan, as the critical neural signal for inducing postsynaptic differentiation and the muscle-specific receptor tyrosine kinase, MuSK, a component of the Agrin receptor, as the transducer for clustering AChRs and activating AChR gene expression at synaptic sites (Burden, 1998;Glass et al, 1996a;Glass et al, 1996b;Glass and Yancopoulos, 1997;Sanes and Lichtman, 2001;Schaeffer et al, 2001;Valenzuela et al, 1995). This neuro-centric view of neuromuscular synapse formation, however, has been challenged by recent experiments, which showed that mammalian muscle is spatially patterned independent of innervation.…”
Section: Introductionmentioning
confidence: 99%
“…For booster injections in 4 -8 wk intervals, the same amount of Nsk2Fc was dissolved in incomplete Freund's adjuvant. This antiserum is referred to as anti-MuSK / Nsk2 to indicate the homology of MuSK cloned from Torpedo, human, rat, and chicken (Jennings et al, 1993;Valenzuela et al, 1995;DeChiara et al, 1996;Glass et al, 1996) with Nsk2 cloned in mouse (Ganju et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…The AChR-aggregating function of agrin requires the synapsespecific receptor tyrosine kinase MuSK, which is tyrosinephosphorylated by agrin isoforms active in AChR aggregation (Valenzuela et al, 1995;DeChiara et al, 1996;Glass et al, 1996). Similarly, phosphorylation of the AChR ␤-subunit seems to be required for agrin-induced AChR aggregation (Wallace et al, 1991;Meier et al, 1995Meier et al, , 1996.…”
mentioning
confidence: 99%